2001
DOI: 10.1083/jcb.152.5.857
|View full text |Cite
|
Sign up to set email alerts
|

α4-Integrin Mediates Neutrophil-Induced Free Radical Injury to Cardiac Myocytes

Abstract: Previous work has demonstrated that circulating neutrophils (polymorphonuclear leukocytes [PMNs]) adhere to cardiac myocytes via β2-integrins and cause cellular injury via the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase enzyme system. Since PMNs induced to leave the vasculature (emigrated PMNs) express the α4-integrin, we asked whether (a) these PMNs also induce myocyte injury via NADPH oxidase; (b) β2-integrins (CD18) still signal oxidant production, or if this process is now coupled to the α4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 42 publications
(51 reference statements)
3
35
1
Order By: Relevance
“…5, untreated neutrophils produced 0.06 Ϯ 0.03 nM/min/10 6 cells of O 2 Ϫ , and Con A-treated neutrophils produced 1.69 Ϯ 0.52 nM/min/10 6 cells. This level is comparable to that produced by murine emigrated neutrophils stimulated with zymosan-activated plasma (34) and less than half of that produced by fMLP-treated human neutrophils (35). Results obtained when Con A plus polymyxin B (10 g/ml, an endotoxin inhibitor) were given to the neutrophils were equivalent to that of Con A alone.…”
Section: Con a Stimulates Neutrophils To Produce Reactive Oxidantsmentioning
confidence: 53%
See 1 more Smart Citation
“…5, untreated neutrophils produced 0.06 Ϯ 0.03 nM/min/10 6 cells of O 2 Ϫ , and Con A-treated neutrophils produced 1.69 Ϯ 0.52 nM/min/10 6 cells. This level is comparable to that produced by murine emigrated neutrophils stimulated with zymosan-activated plasma (34) and less than half of that produced by fMLP-treated human neutrophils (35). Results obtained when Con A plus polymyxin B (10 g/ml, an endotoxin inhibitor) were given to the neutrophils were equivalent to that of Con A alone.…”
Section: Con a Stimulates Neutrophils To Produce Reactive Oxidantsmentioning
confidence: 53%
“…The shedding of L-selectin and increased expression of the ␤ 2 -integrin on neutrophils clearly indicates their activation by Con A, as does their production of reactive oxidants. The regulation of these molecules may be important, as other studies have shown that neutrophil emigration is a ␤ 2 -integrin-dependent process (45) and that oxidant release is limited from neutrophils until after they transmigrate and reach the extracellular space (34). Our results suggest that a second mechanism of action may exist wherein Con A binds directly to neutrophils, presumably via a mannose-sensitive receptor (42), and subsequently activates them independent of other leukocytes.…”
Section: Discussionmentioning
confidence: 73%
“…For assessment of elastase release, supernatants were concentrated with microcons YM3 2-fold before being analyzed by ELISA following the manufacturer's instructions. ) by nonactivated PMNs was determined as the linear rate of superoxide dismutase-inhibitable reduction of cytochrome c as described (18,19). When indicated, PMNs were exposed to 52 nM MPO, 0.5 mg͞ml OZ, and 10 M formyl-MetLeu-Phe, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…18 The generation of superoxide anion by isolated human PMNs was determined as linear rate of superoxide dismutase-inhibitable reduction of cytochrome c as described. 19,20 The measurement was initiated by addition of cytochrome c (5 L, 100 mol/L) and simultaneous application of superoxide dismutase (50 L, 300 U/mL) to the samples.…”
Section: Effect Of Adma On Human Pmn Degranulation and Release Of Oxymentioning
confidence: 99%